From Un posto di vacanza to Il sabato tedesco: constants and novelties in the last Sereni’s works (inOpera Esercizi di lettura su testi contemporanei, 2025)
The study highlights how, in the transition from L’opzione (1964) to Il sabato tedesco (1980), Vittorio Sereni employs images and motifs already present in Un posto di vacanza (1972) and engages in a reflection on the theme of identity with an unusual punctuality; how, moreover, by transferring to Il sabato tedesco a number of poems later included in Stella variabile (1981), he elaborates an original form of prosimetrum.
Keywords: L’opzione; Il sabato tedesco; Un posto di vacanza; Franco Fortini; René Char; Prosimetrum